PENGARUH ISLAMIC CORPORATE GOVERNANCE TERHADAP KECURANGAN PADA PERBANKAN SYARIAH DI INDONESIA - Putri, Rahmawati; Iskandar, Devan; Mutia, Evi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to examine the influence of Islamic corporate governance on fraud in Islamic banks in Indonesia. The population of this study is all Islamic banking in Indonesia in 2016-2020. The sampling technique in this study uses a purposive sampling method with the criteria of the company publishing a complete compliance report on the website of each Islamic bank. 10 Islamic banks become the research sample. This research is quantitative research with a multiple linear regression analysis method. The results of this study indicate that Islamic corporate governance, proxied by the duties and responsibilities of the board of directors, affects fraud in Islamic banking in Indonesia, while the implementation of the duties and responsibilities of the Sharia Supervisory Board has no effect on fraud in Islamic banking in Indonesia. These results contribute valuable insights to the understanding of how Islamic corporate governance can serve as a potent tool in mitigating fraudulent activities within the Islamic banking industry. Moreover, the findings have implications for regulatory bodies and stakeholders aiming to enhance the effectiveness of Islamic banking regulations and governance frameworks, ultimately fortifying the integrity and trustworthiness of Islamic financial institutions.